2000
DOI: 10.3347/kjp.2000.38.3.183
|View full text |Cite
|
Sign up to set email alerts
|

A small-scale survey of intestinal parasite infections among children and adolescents in Legaspi city, the Philippines

Abstract: The Philippines has been known as an endemic area for malaria (Belizario et al., 1997), schistosomiasis japonicum (Mcgarvey et al., 1996) and intestinal capillariasis (Cross, 1992). The Philippines and Southeast Asia are reported as highly prevalent areas of intestinal helminthes as well (Carney et al., 1981; Chai and Hongvanthong, 1998). The Philippines are divided into 3 large provinces, Luzon, Visayas, and Mindanao. Legaspi city is located in Visayas area, 544 km from Manila (Fig. 1). To evaluate the status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 4 publications
0
14
2
Order By: Relevance
“…Belizario et al (2002) mentioned that the cumulative prevalence of intestinal helminth infection in pupils of a public elementary school to be included in a treatment program was 94%. The high prevalence of parasitism shown in this study, although lower than that of other examinations reported from children in communities and schools (Auer, 1990;Lee 2000;Belizario et al, 2002) suggests that there is still much room for the improvement of health delivery and health program implementation. Sanitation practices and water quality should be improved, as these are the major contributory factors for the spread of helminth and protozoan infections.…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…Belizario et al (2002) mentioned that the cumulative prevalence of intestinal helminth infection in pupils of a public elementary school to be included in a treatment program was 94%. The high prevalence of parasitism shown in this study, although lower than that of other examinations reported from children in communities and schools (Auer, 1990;Lee 2000;Belizario et al, 2002) suggests that there is still much room for the improvement of health delivery and health program implementation. Sanitation practices and water quality should be improved, as these are the major contributory factors for the spread of helminth and protozoan infections.…”
contrasting
confidence: 73%
“…For parasitic protozoan infections, the most prevalent parasitic protozoans observed in the children was B. hominis and G. lamblia with respective prevalence of 40.7% and 11.6% (Table 1 & 2). B. hominis infection had a significant prevalence that was not shown even in the more recent studies (Lee et al, 2000;Kim et al, 2003). B. hominis is commonly found in the intestinal tract but it is only lately that it is recognized to cause disease (Neva and Brown, 1994;de Leon, 1998) and thus previous researchers may not have given much attention to it.…”
mentioning
confidence: 97%
“…Polyparasitism (duo and triple infections) was observed in 12% of the infected samples, mainly involving E. Histolytica with one or two other enteric parasites. This is common and widely reported in children elsewhere [58,59]. Seasonal variations are known to affect the prevalence of a number of infections.…”
Section: Discussionmentioning
confidence: 90%
“…It is obvious that high infection rate of A. lumbricoides would affect the growth of children, thus necessitating the medication and education against parasite infection. According to earlier studies on intestinal parasite infection in the Philippines (Cabrera, 1984;Oberst et al, 1987;Lee et al, 2000), the soil-transmitted intestinal helminths such as A. lumbricoides, hookworm, and T. trichiura show more than 30% high infection rates. The present study also revealed similar results.…”
mentioning
confidence: 98%